Cold-resistant non-slip rubber and preparation method thereof
Through the combination of specific components and processes, cold-resistant anti-slip rubber is prepared, which solves the problems of increasing hardness of rubber soles and degradation of anti-slip performance in low-temperature environments, and achieves the improvement of flexibility and anti-slip performance at extremely low temperatures.
Patent Information
- Application Number
- CN202510738808.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2025-08-22
AI Technical Summary
The hardness of conventional rubber sole materials increases, their flexibility decreases, and their anti-slip performance decreases significantly in low temperature environments, resulting in an increase in slip risk and affecting wear comfort and safety.
The specific ratio of diene rubber, cycloane oil, white carbon black, silane coupling agent and polyethylene glycol are used to form a synergistic rubber system through high-temperature first-stage kneading, low-temperature second-stage kneading and segmented vulcanization molding processes to enhance low-temperature flexibility and anti-slip properties.
Maintain the flexibility and effective anti-slip capability of rubber at extremely low temperatures, while improving the mechanical strength and wear resistance of the material to ensure safety and comfort.
Smart Images

Figure BDA0005434072260000131
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber, and in particular to a cold-resistant anti-slip rubber and a preparation method thereof. Background Art
[0002] As a key component of footwear that comes into direct contact with the ground, the performance of the sole is directly related to wearing comfort, safety, and durability. Rubber materials, due to their excellent elasticity, wear resistance, and adjustable friction properties, are widely used in the manufacture of various soles, particularly in sports shoes, outdoor shoes, and specialized protective footwear. However, conventional rubber sole materials often exhibit significant performance deficiencies in low-temperature environments.
[0003] When the ambient temperature drops below zero degrees Celsius, especially in extremely cold regions or seasons, the mobility of the molecular segments of traditional rubber sole materials decreases dramatically. This leads to a significant increase in the hardness of the sole material, a significant decrease in flexibility, and even embrittlement. This change not only seriously affects wearing comfort, making the sole stiff and difficult to bend, but more importantly, it directly weakens the sole's anti-slip performance. The hard sole has a reduced effective contact area on ice, snow, or cold, wet roads, and its deformability is reduced, making it difficult to form a good mechanical interlock and effective friction with irregular surfaces. As a result, the friction coefficient is significantly reduced, which can easily lead to slip accidents and pose a serious threat to the user's personal safety. Summary of the Invention
[0004] The purpose of the present invention is to overcome the above-mentioned defects or problems existing in the background technology and provide a cold-resistant anti-slip rubber and a preparation method thereof, wherein the cold-resistant anti-slip rubber can maintain good anti-slip performance in a low temperature environment.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] Technical Solution 1: A cold-resistant anti-slip rubber comprising the following components: 80-110 parts by weight of diene rubber; 5-8 parts by weight of cyclohexane oil; 35-45 parts by weight of white carbon black; 5-6 parts by weight of a silane coupling agent; 3-4 parts by weight of polyethylene glycol with a molecular weight range of 3500-4400; and a vulcanization system.
[0007] Technical Solution 2 based on Technical Solution 1: The vulcanization system includes: an active agent, including 6-7 parts by weight of active zinc oxide and 0.5-1 parts by weight of stearic acid; a vulcanizing agent, which is 2-3 parts by weight of a sulfur masterbatch pre-dispersed with an inert carrier; and a composite accelerator, comprising 1.5-2.0 parts by weight of N-cyclohexyl-2-benzothiazole sulfenamide, 0.5-1.0 parts by weight of tetramethylthiuram disulfide pre-dispersed with an inert carrier, and 1.5-2.0 parts by weight of N-tert-butyl-2-benzothiazole sulfenamide pre-dispersed with an inert carrier.
[0008] Technical solution three based on technical solution one: the diene rubber is butadiene rubber, and its cis-1,4 structure content is greater than or equal to 96%.
[0009] Technical solution 4 based on technical solution 1: the silane coupling agent is a sulfur-containing silane coupling agent.
[0010] Technical solution 5 based on technical solution 1: further comprising 3-5 parts by weight of hydrogenated petroleum resin, wherein the softening point of the hydrogenated petroleum resin is 100±5°C.
[0011] Technical solution 6 based on technical solution 1: further comprising 4-5 parts by weight of an anti-cracking agent, wherein the anti-cracking agent is a compound of microcrystalline wax and a chemical antiozonant.
[0012] Technical solution 7 based on technical solution 1: further comprising 3-4 parts by weight of a composite internal anti-emetic cream, wherein the anti-emetic cream is composed of a high molecular weight fatty acid ester and a polyol ester.
[0013] In addition, the present invention also provides technical solution eight: a method for preparing cold-resistant and anti-slip rubber, characterized in that it includes the following steps: high-temperature one-stage mixing: mixing the diene rubber, the cyclohexane oil, the white carbon black, the silane coupling agent, the polyethylene glycol and other additives except the vulcanization system in an internal mixer, and the discharge temperature is controlled in the range of 100-130°C to obtain a masterbatch; low-temperature two-stage mixing: cooling the masterbatch obtained in the previous step to a rubber temperature below 60°C, adding the vulcanization system for mixing, the mixing temperature is 50-65°C, and ensuring that the rubber temperature does not exceed 90°C to obtain a final rubber mix; sheeting and parking: the final rubber mix obtained in the previous step is rolled out into sheets and parked in an environment with controlled room temperature and relative humidity for 12-24 hours; and vulcanization molding: placing the rubber after parking in the previous step in a mold and vulcanizing and molding at a temperature of 150-170°C and a pressure of 8-15MPa.
[0014] Technical solution nine based on technical solution eight: the debinding temperature in the high-temperature first-stage mixing is controlled at 115±5°C.
[0015] Technical Solution 10 based on Technical Solution 8: The vulcanization molding adopts a segmented vulcanization process, including: performing a first stage vulcanization for 180-220 seconds at a temperature of 160°C and a pressure of 12 MPa, and then continuing with a second stage vulcanization for 450-510 seconds without changing the temperature and pressure.
[0016] From the above description of the present invention, it can be seen that compared with the prior art, the present invention has the following beneficial effects:
[0017] Technical solution 1 provides a cold-resistant and anti-slip rubber, which achieves a significant breakthrough in the cold resistance and anti-slip properties of rubber materials by compounding multiple components in a specific ratio.
[0018] First, the combination of 80-110 parts by weight of diene rubber and 5-8 parts by weight of naphthenic oil forms the basis of the material's excellent low-temperature performance. Diene rubber itself has a certain low-temperature motion capability due to its molecular chain structure characteristics. As a low-temperature plasticizer, naphthenic oil's small molecules penetrate into the rubber macromolecular chains, effectively increasing the free volume of the molecular chains and weakening the interchain forces, thereby significantly reducing the glass transition temperature of the entire rubber system. This basic combination directly gives the rubber the ability to maintain flexibility at low temperatures, which is the first step in overcoming the common technical difficulties of conventional rubber being prone to hardening and brittle cracking in low-temperature environments, resulting in a sharp decline in anti-slip performance. However, relying solely on the combination of the two, although low-temperature performance can be improved, the mechanical strength and wear resistance of the material are often greatly sacrificed due to the introduction of plasticizers in the pursuit of cold resistance. This is a common technical understanding in the field, that is, there is a trade-off between low-temperature performance and mechanical strength.
[0019] The key innovation and non-obviousness of this technical solution lies in the synergistic effect of 35-45 parts by weight of carbon black, 5-6 parts by weight of silane coupling agent and 3-4 parts by weight of polyethylene glycol of a specific molecular weight. This combination not only compensates for the strength loss caused by plasticization, but also produces a synergistic enhancement effect.
[0020] As the main reinforcing filler, carbon black can significantly improve the strength and wear resistance of rubber due to its high specific surface area and active points. However, in a system containing a large amount of plasticizer, the interfacial compatibility between carbon black and the non-polar diene rubber matrix will deteriorate, and the carbon black particles themselves are prone to agglomeration, resulting in low reinforcement efficiency and even becoming stress concentration points. At the same time, the high amount of carbon black filling itself will increase the low-temperature hardness of the material, which is contrary to the goal of pursuing extreme cold resistance. This solution fundamentally changes the interaction mode between carbon black and the rubber matrix by introducing 5-6 parts by weight of silane coupling agent. The molecular structure of the silane coupling agent enables one end to chemically bond or form strong physical adsorption with active groups such as hydroxyl groups on the surface of carbon black, while the other end (usually a sulfur-containing functional group) can form a stable chemical crosslink with the molecular chain of the diene rubber during the vulcanization process. The formation of this "molecular bridge" greatly strengthens the interfacial bonding between the carbon black filler and the rubber matrix. The direct result of this strong interfacial bonding is that even in the presence of naphthenic oil, carbon black can still efficiently transfer stress from the rubber matrix to itself, significantly improving the material's tensile strength, tear strength, and wear resistance, far exceeding systems that use no or inefficient coupling agents. This is itself an unexpected technical effect, as plasticizers are conventionally expected to significantly weaken the reinforcing effect of fillers. The effective effect of the silane coupling agent ensures that high carbon black loadings not only do not excessively degrade low-temperature performance, but actually provide a solid foundation for the material to maintain its shape stability and wear resistance at low temperatures.
[0021] Furthermore, the addition of 3-4 parts by weight of polyethylene glycol in a specific molecular weight range (3500-4400) does not simply act as a processing aid, but rather further strengthens and optimizes the aforementioned carbon black-silane coupling agent synergistic system, demonstrating a deeper synergistic effect. Polyethylene glycol plays the following key roles in this system: First, it significantly improves the dispersion of carbon black in the rubber matrix. Uniform dispersion of carbon black is a prerequisite for achieving its maximum reinforcing potential. Through the interaction between its polar end and the carbon black surface and the good compatibility of its chain segments with the rubber matrix, polyethylene glycol effectively prevents secondary agglomeration of carbon black particles, creating conditions for the silane coupling agent to more fully contact and react with the carbon black surface. Second, polyethylene glycol of a specific molecular weight acts as a promoter and pH buffer for the hydrolysis and condensation reactions of the silane coupling agent, improving the efficiency and extent of the reaction between the silane coupling agent and the carbon black surface, thereby forming a more complete and stronger filler-rubber interface. This enhanced dispersion and more efficient coupling, aided by polyethylene glycol, maximizes the reinforcing potential of carbon black, contributing to overall mechanical properties beyond the expected sum of the individual components. As a result, while the material achieves excellent low-temperature flexibility, its wear resistance and strength not only do not decline significantly as expected by technical bias, but are significantly enhanced, which is crucial for demanding anti-slip applications.
[0022] In summary, this technical solution does not simply mix components known to have specific functions, but rather constructs a multi-level synergistic system through the complex interactions between the components. Diene rubber and cyclohexane oil lay the foundation for low-temperature performance; while the innovative combination of carbon black, silane coupling agent and polyethylene glycol of a specific molecular weight overcomes the inherent contradiction between low-temperature performance and mechanical strength in an unexpected way. This synergistic effect allows the final rubber material to maintain excellent flexibility and effective anti-slip ability at extremely low temperatures. At the same time, its mechanical strength and wear resistance are sufficient to cope with harsh operating environments, resulting in a cold-resistant and anti-slip rubber with comprehensive performance far exceeding expectations.
[0023] Technical Solution 2 defines a specific vulcanization system. The activators (activated zinc oxide and stearic acid) effectively activate the accelerator, improving the efficiency of the vulcanization reaction and fostering the formation of a denser, more uniform cross-linked network, which is beneficial for enhancing the rubber's comprehensive physical and mechanical properties and aging resistance. The sulfur masterbatch, pre-dispersed with an inert carrier as a vulcanizing agent, ensures uniform sulfur dispersion in the rubber, avoiding localized over- or under-sulfurization, resulting in a vulcanized rubber with uniform properties, which is crucial for the performance stability and reliability of the final product. The use of composite accelerators (N-cyclohexyl-2-benzothiazole sulfonamide, tetramethylthiuram disulfide pre-dispersed with an inert carrier, and N-tert-butyl-2-benzothiazole sulfonamide pre-dispersed with an inert carrier) can precisely control the scorch time, vulcanization rate and flatness of the vulcanization process through the synergistic effect of different types of accelerators, which helps to form a structurally optimized cross-linked network. For example, while ensuring processing safety, it is possible to form single sulfur bonds and disulfide bonds with better thermal stability, thereby improving the heat aging resistance, fatigue resistance and dynamic mechanical properties of the vulcanized rubber, and ensuring that the rubber maintains its cold resistance and anti-slip properties in a wide temperature range and long-term use.
[0024] Technical Solution 3 specifically defines diene rubber as cis-1,4-butadiene rubber with a cis-1,4 structure content of 96% or greater. This high-cis-content cis-butadiene rubber exhibits a low glass transition temperature, excellent elasticity, and outstanding wear resistance. Its highly regular molecular chain structure imparts exceptional low-temperature flexibility. Using this type of cis-butadiene rubber directly enhances the rubber material's ability to maintain compliance and effective friction in extremely low-temperature conditions, significantly improving the final product's cold resistance and low-temperature anti-slip performance.
[0025] In Technical Solution 4, the silane coupling agent is specifically defined as a sulfur-containing silane coupling agent. Sulfur-containing silane coupling agents (such as the commonly used Si-69) have bifunctional characteristics. One end of the silane coupling agent can react with the active groups on the surface of fillers such as carbon black to form a chemical bond, and the sulfur-containing functional group at the other end can undergo a co-vulcanization reaction with the rubber molecular chain during the vulcanization process. This chemical bridging effect greatly improves the dispersion of the filler in the rubber matrix, reduces the interaction between filler particles (i.e., the Payne effect), reduces the hysteresis loss of the rubber compound, and significantly enhances the reinforcing effect of the filler on the rubber. Its technical effect is to comprehensively improve the tensile strength, tensile stress, wear resistance and tear strength of the vulcanized rubber. For anti-slip rubber, this enhanced filler-matrix interaction and optimized dispersion state help to improve the friction properties of the rubber surface, especially the grip under wet conditions, and improve the durability of these properties under long-term use and temperature changes.
[0026] Technical Solution 5 further stipulates that the rubber composition contains 3-5 parts by weight of hydrogenated petroleum resin, and its softening point is 100±5°C. The addition of hydrogenated petroleum resin can first improve the processing properties of the rubber, such as reducing the Mooney viscosity of the mixed rubber and improving fluidity. At the same time, as a reinforcing resin, it can increase the hardness and tensile stress of the vulcanized rubber, and may further enhance the overall performance of the material by improving the compatibility between different rubber components or between rubber and fillers. The hydrogenation treatment improves the thermal stability and color stability of the resin, reducing the possibility of degradation or yellowing during processing and use. In the specific application of anti-slip rubber, the addition of this type of resin can adjust the viscoelasticity of the rubber surface, which may have a positive effect on the friction coefficient on the specific contact surface, helping to improve the anti-slip effect. Its specific softening point ensures that the resin can effectively function within the processing temperature and final use temperature range of the rubber.
[0027] Technical Solution 6 further specifies that the rubber composition contains 4-5 parts by weight of an anti-cracking agent, which is a compound of microcrystalline wax and a chemical anti-ozonant. Microcrystalline wax, as a physical protective agent, can migrate to the surface of the rubber product after vulcanization, forming a continuous, flexible protective film. This film can effectively block the erosion of ozone on the main rubber material and has a certain inhibitory effect on the propagation of cracks caused by dynamic flexural fatigue. Chemical anti-ozonants (such as paraphenylenediamine antioxidants) protect rubber through a chemical reaction mechanism. They can preferentially react with ozone or scavenge free radicals produced after ozone attacks the double bonds of rubber, thereby preventing or slowing down the breakage and aging of the rubber molecular chain. This combination of physical and chemical protection can provide more comprehensive and lasting protection against ozone aging and dynamic fatigue cracking, significantly improving the service life and performance stability of rubber products under outdoor exposure or dynamic stress conditions, and ensuring that the anti-slip surface maintains its integrity during long-term use.
[0028] Technical Solution 7 further defines a rubber composition comprising 3-4 parts by weight of a composite internal anti-emetic creamer consisting of a high molecular weight fatty acid ester and a polyol ester. Blooming refers to the phenomenon in which rubber compounding ingredients (such as sulfur, accelerators, antioxidants, waxes, etc.) migrate to the surface of a product after vulcanization or during storage due to reduced solubility or oversaturation in the rubber. Blooming not only affects the appearance of the product, but more importantly, it changes the physical and chemical properties of the product surface, such as reducing the surface friction coefficient, thereby weakening the anti-slip effect. The composite internal anti-emetic creamer consisting of a high molecular weight fatty acid ester and a polyol ester effectively inhibits the migration of these easily migratable compounding ingredients to the product surface by increasing their solubility in the rubber matrix or forming a stable complex with them. The technical effect is to maintain the cleanliness and original design performance of the rubber product surface, especially to maintain the stable friction characteristics of the anti-slip surface, while improving the aesthetics and quality stability of the product.
[0029] Technical Solution 8 provides a method for preparing cold-resistant and anti-slip rubber. The method includes high-temperature one-stage mixing, low-temperature two-stage mixing, sheeting and parking, and vulcanization molding steps. High-temperature one-stage mixing (draining temperature 100-130°C) mixes diene rubber, cyclohexane oil, carbon black, silane coupling agent, polyethylene glycol and other non-vulcanization system additives to ensure the full dispersion of fillers such as carbon black and promote the effective reaction of silane coupling agent with the filler surface, laying the foundation for the formation of a strong filler-rubber interface bond. Low-temperature two-stage mixing (the first stage masterbatch is cooled to below 60°C, the mixing temperature is 50-65°C, and the rubber temperature does not exceed 90°C) is added to the vulcanization system. The low-temperature operation is to prevent the rubber from premature vulcanization (scorching) before molding, thereby ensuring the safety of the processing process. Sheeting and parking (parking for 12-24 hours at room temperature and relative humidity controlled environment) help to relax the internal stress of the rubber, further evenly diffuse the compounding agents, and stabilize the performance of the rubber. The final vulcanization process (150-170°C, 8-15MPa) crosslinks the rubber, forming a stable three-dimensional network structure that gives the product its ultimate shape, elasticity, and mechanical properties. This segmented, precisely controlled preparation method maximizes the effectiveness of each component, ensuring optimized microstructure and optimal macroscopic properties, resulting in the stable production of high-quality rubber products with excellent cold resistance and slip resistance.
[0030] In Technical Solution 9, the discharge temperature in the high-temperature first-stage mixing is further precisely controlled at 115±5°C. This narrower temperature control range (110-120°C) is particularly critical for optimizing the reaction efficiency and degree of silane coupling agents with fillers such as carbon black. Within this specific temperature range, the silanization reaction of the silane coupling agent can proceed more fully, while effectively avoiding excessive degradation of the polymer chain or early decomposition of certain additives that may be caused by excessively high temperatures. The technical effect is to further enhance the interfacial bonding strength between the filler and the rubber matrix and the uniformity of the filler dispersion, thereby more effectively enhancing the reinforcement effect of the rubber and ensuring the consistency and stability of product performance between batches, which is crucial for ultimately obtaining reliable and high-performance cold-resistant and anti-slip rubber.
[0031] In Technical Solution 10, the vulcanization molding process is specifically defined as segmented vulcanization: at a temperature of 160°C and a pressure of 12MPa, the first stage vulcanization is carried out for 180-220 seconds, and then the second stage vulcanization is carried out for 450-510 seconds without changing the temperature and pressure. This segmented or extended vulcanization process with a clear intermediate inspection point is intended to achieve a more complete and optimized vulcanization effect. The first stage of vulcanization (180-220 seconds) may mainly allow the rubber to fully flow and fill the mold cavity, achieve preliminary shaping and form a certain cross-linked network. The subsequent second stage of long-term vulcanization (450-510 seconds) ensures the full progress of the vulcanization reaction, helps to form a more uniform, more stable, and less defective three-dimensional cross-linked network structure, and may promote the optimization of sulfur bond types (for example, some polysulfide bonds are converted to more stable single sulfur bonds and disulfide bonds, improving heat resistance and aging resistance). Its technical effect is to further improve the comprehensive physical and mechanical properties, dimensional stability, reduce internal stress, and possibly enhance the dynamic performance and durability of the vulcanized rubber, thereby maximizing the potential of the formula design and ensuring that the cold-resistant and anti-slip rubber achieves the best performance. DETAILED DESCRIPTION
[0032] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are preferred embodiments of the present invention and should not be considered as excluding other embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0033] In the claims and description of the present invention, unless otherwise clearly defined, the use of terms such as "first", "second" or "third" is for distinguishing different objects rather than for describing a specific order.
[0034] In the claims and description of the present invention, if the terms "include", "have" and their variations are used, they are intended to mean "including but not limited to".
[0035] The invention relates to a cold-resistant anti-skid rubber and a preparation method thereof. The cold-resistant anti-skid rubber comprises the following components: 80-110 parts by weight of diene rubber; 5-8 parts by weight of cyclohexane oil; 35-45 parts by weight of carbon black; 5-6 parts by weight of a silane coupling agent; 3-4 parts by weight of polyethylene glycol having a molecular weight range of 3500-4400; and a vulcanization system.
[0036] The vulcanization system includes: an active agent, including 6-7 parts by weight of active zinc oxide and 0.5-1 parts by weight of stearic acid; a vulcanizing agent, which is 2-3 parts by weight of sulfur masterbatch pre-dispersed with an inert carrier; and a composite accelerator, which includes 1.5-2.0 parts by weight of N-cyclohexyl-2-benzothiazole sulfenamide, 0.5-1.0 parts by weight of tetramethylthiuram disulfide pre-dispersed with an inert carrier, and 1.5-2.0 parts by weight of N-tert-butyl-2-benzothiazole sulfenamide pre-dispersed with an inert carrier.
[0037] Specifically, the diene rubber is cis-1,4-butadiene rubber, with a cis-1,4 structure content of 96% or greater. For example, rare earth cis-1,4-butadiene rubber, such as BR9000, Nd-BR40 produced by PetroChina Lanzhou Petrochemical Company, or BR9000 produced by Yanshan Petrochemical Company can be used. Their Mooney viscosity (ML1+4@100°C) is typically in the range of 40-55.
[0038] Specifically, the naphthenic oil may be, for example, naphthenic rubber oils such as KN4006 or KN4010 produced by Sinopec, which have good low-temperature performance and low aromatic content.
[0039] Specifically, the carbon black can be selected from highly dispersed precipitated silica, such as Ultrasil VN3 or Ultrasil 7000GR from Evonik, or Zeosil 1165MP or Zeosil Premium 200MP from Solvay, which generally have a BET specific surface area of 150-250 m 2 / g range to provide excellent reinforcement performance and low rolling resistance characteristics.
[0040] Specifically, the silane coupling agent is a sulfur-containing silane coupling agent. Specifically, for example, Si-69 (chemical name bis-[3-(triethoxysilyl)-propyl]-tetrasulfide) or Si-75 (chemical name bis-[3-(triethoxysilyl)-propyl]-disulfide) in liquid or solid powder form (e.g., a pre-dispersion blended with carbon black) can be used, and are manufactured by companies such as Evonik or Dow Corning.
[0041] Specifically, the molecular weight of the polyethylene glycol is in the range of 3500-4400. Specifically, for example, polyethylene glycol with the brand name PEG-4000 can be used, and its average molecular weight is within this range. Commercially available products are generally in the form of flakes or powders, and are produced by companies such as BASF and Dow Chemical.
[0042] Specifically, the active agent includes 6-7 parts by weight of active zinc oxide. Specifically, for example, a specific surface area greater than 30m 2 / g of indirect or direct activated zinc oxide, such as the "Lianbo" brand activated zinc oxide produced by Jiangsu Lianbo Chemical Co., Ltd.
[0043] Specifically, the active agent further comprises 0.5-1 parts by weight of stearic acid. Specifically, for example, industrial grade 1 stearic acid (1801 type) can be selected, which is mainly composed of a mixture of stearic acid and palmitic acid and complies with GB / T 9103-2017 standard.
[0044] Specifically, the vulcanizing agent is 2-3 parts by weight of a sulfur masterbatch pre-dispersed with an inert carrier. Specifically, for example, a sulfur masterbatch with a brand name of S-80 or IS-80 can be used, which contains 80% sulfur, 20% inert carrier (such as EPDM or SBR), and a dispersant pre-dispersed therein, such as Rhenogran S-80 from Rhein Chemie.
[0045] Specifically, the composite accelerator comprises 1.5-2.0 parts by weight of N-cyclohexyl-2-benzothiazolesulfenamide, specifically, accelerator CZ or CBS, for example, accelerator CBS produced by Shengao Chemical Technology Co., Ltd.
[0046] Specifically, the composite accelerator further comprises 0.5-1.0 parts by weight of tetramethylthiuram disulfide pre-dispersed with an inert carrier. Specifically, for example, an accelerator masterbatch with the brand name TMTD-80 or TT-80 can be used, which comprises 80% tetramethylthiuram disulfide (accelerator TMTD or TT) pre-dispersed with 20% of an inert carrier and a dispersant, such as Rhenogran TMTD-80 from Rhein Chemie.
[0047] Specifically, the composite accelerator further comprises 1.5-2.0 parts by weight of N-tert-butyl-2-benzothiazolesulfenamide pre-dispersed with an inert carrier. Specifically, for example, an accelerator masterbatch with the brand name TBBS-80 or NS-80 can be used, which comprises 80% N-tert-butyl-2-benzothiazolesulfenamide (accelerator TBBS or NS) pre-dispersed with 20% of an inert carrier and a dispersant, such as Rhenogran TBBS-80 from Rhein Chemie.
[0048] Specifically, the cold-resistant anti-slip rubber further comprises 3-5 parts by weight of a hydrogenated petroleum resin having a softening point of 100±5°C. Specifically, for example, a hydrogenated C9 petroleum resin of the Escorez 5300 series (e.g., Escorez 5300 or Escorez 5320) manufactured by ExxonMobil, or a similar hydrogenated alicyclic hydrocarbon resin having a softening point in the range of 95-105°C, can be used.
[0049] Specifically, the cold-resistant, non-slip rubber also includes 4-5 parts by weight of an anti-cracking agent, which is a compound of microcrystalline wax and a chemical antiozonant. Specifically, the microcrystalline wax can be a rubber protective wax with a melting point in the range of 60-75°C, such as paraffin grade 64 produced by Sinopec, or microcrystalline wax with similar properties. The chemical antiozonant can be N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (6PPD or antioxidant 4020) or N-isopropyl-N'-phenyl-p-phenylenediamine (IPPD or antioxidant 4010NA), such as antioxidant 4020 produced by Shengao Chemical Technology Co., Ltd. When compounded, the weight ratio of microcrystalline wax to chemical antiozonant can be, for example, 3:1 to 1:1.
[0050] Specifically, the cold-resistant, anti-slip rubber also includes 3-4 parts by weight of a composite internal anti-emetic cream composed of a high-molecular-weight fatty acid ester and a polyol ester. Specifically, the high-molecular-weight fatty acid ester can be an ester mixture of metal soaps such as zinc stearate and calcium stearate with a high-molecular-weight fatty alcohol; the polyol ester can be, for example, pentaerythritol stearate or glycerol monostearate. Commercially available composite anti-emetic creams, such as Struktol A60 or similar products, are typically proprietary blends of these components designed to improve the solubility and compatibility of multiple compounding ingredients in the rubber.
[0051] In addition, the preparation method of the cold-resistant anti-slip rubber involved in the present invention comprises the following steps:
[0052] High-temperature, single-stage mixing: The diene rubber, naphthenic oil, silica, silane coupling agent, polyethylene glycol, and other additives (excluding the vulcanization system) are mixed in an internal mixer at a discharge temperature of 100-130°C to produce a masterbatch. This step is typically performed in an intermeshing or tangential internal mixer, such as an X(S)N-75 or X(S)N-110. The general order of addition is: first add the diene rubber and masticate (e.g., for 1-2 minutes), then add silica, silane coupling agent, and polyethylene glycol in batches, followed by naphthenic oil and other additives. The internal mixer rotor speed can be controlled at 30-50 rpm, the ram pressure can be set at 0.5-0.8 MPa, and the fill factor is typically 0.7-0.8. The total mixing time depends on the specific equipment and rubber compound, usually 8-15 minutes to ensure that the silica is fully dispersed and the silane coupling agent reacts fully with the silica.
[0053] Low-temperature second-stage mixing: After the first-stage masterbatch obtained in the previous step is cooled to a temperature below 60°C, the vulcanization system is added and mixed at a temperature of 50-65°C, ensuring that the temperature does not exceed 90°C, to obtain the final rubber mix. Specifically, cooling is typically achieved by immersing the first-stage masterbatch in a cooling water tank or air-cooling it on a cooling conveyor, ensuring that the internal temperature of the rubber mix is sufficiently reduced. This step is typically performed on an open mixing mill (open mill), such as one with a roller diameter of 400mm or 550mm. The roller temperature of the open mill is controlled within the stated range using cooling water. The first-stage masterbatch is first rolled and thinned on the roller (e.g., 3-5 times), followed by the vulcanization system (sulfur masterbatch, accelerator masterbatch, and microcrystalline wax as an anti-cracking agent, if not already added in the first stage). Ensure even distribution of the ingredients, and ensure uniform mixing by means of triangular bagging or cutting. The mixing time is usually 8-12 minutes to ensure that the vulcanization system is evenly dispersed and the temperature of the rubber compound is effectively controlled.
[0054] Sheeting and storage: The final rubber mix obtained in the previous step is rolled out into sheets and stored in an environment with controlled room temperature and relative humidity for 12-24 hours. Specifically, the final rubber mix is rolled into sheets with a certain thickness (for example, 3-10mm, depending on the requirements of subsequent vulcanized products) through an open mill, or is more accurately sheeted through a calender. After sheeting, the sheets should be placed flat on a clean tray or shelf to avoid sticking to each other or contamination. The room temperature of the storage environment is usually controlled at 23±2℃, and the relative humidity is controlled at 50±5%. The purpose of storage is to further evenly diffuse the compounding ingredients inside the rubber, eliminate internal stress, and stabilize the physical properties and processing properties of the rubber.
[0055] Vulcanization molding: Place the rubber material after the previous step in the mold, and perform vulcanization molding at a temperature of 150-170°C and a pressure of 8-15MPa. Specifically, design the corresponding metal mold (usually a steel mold) according to the shape and size of the product. Cut the parked film according to the required weight or size and place it in the preheated mold. Vulcanization is usually carried out on a flat vulcanizer, which can provide precise temperature and pressure control. The temperature of the hot plate of the vulcanizer is set at 150-170°C, and the applied pressure is controlled at 8-15MPa through the hydraulic system (this pressure usually refers to the pressure per unit area in the mold cavity, which needs to be converted according to the total area of the mold and the total pressure of the vulcanizer).
[0056] The binder removal temperature during the high-temperature first stage of mixing is controlled at 115±5°C. During operation, the binder removal temperature can be precisely controlled by adjusting the cooling water flow rate, rotor speed, or mixing time of the internal mixer. Temperature monitoring is typically performed using an insert thermocouple or infrared thermometer.
[0057] The vulcanization molding adopts a segmented vulcanization process, including: at a temperature of 160°C and a pressure of 12MPa, performing the first stage vulcanization for 180-220 seconds, and then continuing the second stage vulcanization for 450-510 seconds without changing the temperature and pressure. Specifically, after the first stage vulcanization is completed, a short exhaust operation (such as instant mold opening and then mold closing for 1-3 seconds) can be performed as needed to remove the volatile gas in the mold cavity, and then enter the second stage vulcanization. During the entire vulcanization process, the temperature and pressure of the flat vulcanizing press need to be kept constant. After the vulcanization is completed, the mold is cooled to a certain temperature (for example, below 80°C) while maintaining the pressure, and then the mold is opened to remove the parts to reduce product deformation.
[0058] The technical solutions of the present invention will be described clearly and completely below in conjunction with the embodiments so that those skilled in the art can better understand the present invention. Obviously, the embodiments described are only some preferred embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0059] Unless otherwise stated, all raw materials and reagents used in the examples of the present invention are commercially available industrial products or analytically pure products.
[0060] 1. Raw materials
[0061] The main raw materials used in the examples and comparative examples of the present invention and their specifications / brands and manufacturers / suppliers are as follows:
[0062] Cis-butadiene rubber (Nd-BR): brand BR9000, cis-1,4 content ≥96% (Yanshan Petrochemical).
[0063] Naphthenic oil: brand KN4006 (Sinopec).
[0064] Silica (highly dispersed precipitation method): brand Ultrasil VN3 (Evonik).
[0065] Silane coupling agent (sulfur-containing): brand Si-69, chemical name bis-[3-(triethoxysilyl)-propyl]-tetrasulfide (Evonik).
[0066] Polyethylene glycol (PEG): brand PEG-4000, average molecular weight range 3500-4400 (BASF).
[0067] Active zinc oxide: "Lianbo" brand, industrial grade, specific surface area ≥30m 2 / g(Jiangsu Lianbo Chemical Co., Ltd.).
[0068] Stearic acid: industrial grade (1801 type).
[0069] Sulfur masterbatch: Rhenogran S-80, containing 80% sulfur (Rhein Chemie).
[0070] Accelerator CBS: N-cyclohexyl-2-benzothiazole sulfenamide (Sangao Chemical Technology Co., Ltd.).
[0071] Accelerator TMTD masterbatch: Rhenogran TMTD-80, containing 80% tetramethylthiuram disulfide (Rhein Chemie).
[0072] Accelerator TBBS masterbatch: Rhenogran TBBS-80, containing 80% N-tert-butyl-2-benzothiazole sulfenamide (Rhein Chemie).
[0073] Hydrogenated petroleum resin: brand Escorez 5300, softening point 100±5℃ (ExxonMobil).
[0074] Microcrystalline wax: paraffin brand 64#, rubber protective wax, melting point 60-75℃ (Sinopec).
[0075] Chemical antiozonant (6PPD): Antioxidant 4020, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine (Sangao Chemical Technology Co., Ltd.).
[0076] Composite internal anti-emetic cream: Struktol A60, a complex of high molecular weight fatty acid esters and polyol esters.
[0077] Styrene-butadiene rubber (SBR): used for comparative example, brand SBR 1502.
[0078] Aromatic oil (DAE): used for comparative examples, rubber filler oil.
[0079] Conventional silica: used in comparative examples, brand name Zeosil 175C.
[0080] Accelerator DPG: used in comparative example, diphenylguanidine.
[0081] Sulfur powder: used for comparative example, industrial grade.
[0082] 2. Preparation of rubber composition
[0083] Unless otherwise specified, the rubber compositions in the following examples and comparative examples were prepared according to the following method:
[0084] High-temperature, first-stage mixing: Place cis-butadiene rubber (or a blend of styrene-butadiene rubber and cis-butadiene rubber) in an X(S)N-75 internal mixer and masticate for 1-2 minutes. Then, add silica (or conventional silica), silane coupling agent (if present), polyethylene glycol (if present), hydrogenated petroleum resin (if present), chemical antiozonant (if present), composite internal anti-emetic cream (if present), and naphthenic oil (or aromatic oil) in sequence and continue mixing. Maintain the internal mixer rotor speed at 40 rpm, the top bolt pressure at 0.6 MPa, and the fill factor at 0.75. The total mixing time is approximately 10-12 minutes. Ensure the discharge temperature is controlled at 115±5°C (110-120°C). This produces a first-stage masterbatch.
[0085] Low-temperature second-stage mixing: Cool the masterbatch stage one on a cooling conveyor and allow it to rest until the compound temperature drops below 60°C. The cooled masterbatch stage one is then placed in a Φ400mm open mill, with the roller temperature controlled at 50-65°C. Roller wrapping and 3-5 thin passes are performed, followed by the addition of activated zinc oxide, stearic acid, sulfur masterbatch (or sulfur powder), accelerator CBS, accelerator TMTD masterbatch, accelerator TBBS masterbatch (or accelerator DPG), and microcrystalline wax (if any). Ensure uniform mixing by means of triangular wrapping and cutting. Mix for approximately 10 minutes, ensuring the final compound temperature does not exceed 90°C. This results in the final rubber mix.
[0086] Sheeting and storage: The final mixed rubber is rolled into a sheet with a thickness of about 5 mm through an open mixing mill and stored flat at room temperature of 23±2°C and relative humidity of 50±5% for 24 hours.
[0087] Vulcanization Molding: The film is cut to the desired size after storage and placed in a preheated mold for vulcanization on a flatbed vulcanizer. Vulcanization conditions are: temperature 160°C, pressure 12 MPa. A staged vulcanization process is used: the first stage vulcanization lasts 200 seconds, followed by a 1-2 second mold opening to vent air, and then the mold is closed for the second stage vulcanization of 480 seconds. After vulcanization is complete, the mold is cooled to below 80°C while maintaining pressure before opening the mold to remove the part.
[0088] 3. Formulas of Examples and Comparative Examples (Unit: parts by weight)
[0089] Example 1
[0090] 100 parts of butadiene rubber (Nd-BR, BR9000), 6.3 parts of naphthenic oil (KN4006), 38 parts of white carbon black (UltrasilVN3), 5.5 parts of silane coupling agent (Si-69), 3.3 parts of polyethylene glycol (PEG-4000), 6.6 parts of active zinc oxide ("Lianbo" brand), 0.63 parts of stearic acid (1801 type), 2.5 parts of sulfur masterbatch (Rhenogran S-80), 1.88 parts of accelerator CBS, 0.63 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 1.63 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 4 parts, microcrystalline wax (paraffin brand No. 64#) 3 parts, chemical antiozonant (antioxidant 4020) 1.5 parts, composite internal anti-emetic cream (Struktol A60) 3.1 parts.
[0091] Example 2
[0092] 80 parts of butadiene rubber (Nd-BR, BR9000), 5 parts of naphthenic oil (KN4006), 35 parts of white carbon black (Ultrasil VN3), 5 parts of silane coupling agent (Si-69), 3 parts of polyethylene glycol (PEG-4000), 6 parts of active zinc oxide ("Lianbo" brand), 0.5 parts of stearic acid (1801 type), 2 parts of sulfur masterbatch (Rhenogran S-80), 1.5 parts of accelerator CBS, 0.5 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 1.5 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 3 parts, microcrystalline wax (paraffin brand No. 64#) 2.8 parts, chemical antiozonant (antioxidant 4020) 1.2 parts, composite internal anti-emetic cream (Struktol A60) 3 parts.
[0093] Example 3
[0094] 110 parts of butadiene rubber (Nd-BR, BR9000), 8 parts of naphthenic oil (KN4006), 45 parts of white carbon black (UltrasilVN3), 6 parts of silane coupling agent (Si-69), 4 parts of polyethylene glycol (PEG-4000), 7 parts of active zinc oxide ("Lianbo" brand), 1 part of stearic acid (1801 type), 3 parts of sulfur masterbatch (Rhenogran S-80), 2.0 parts of accelerator CBS, 1.0 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 2.0 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 5 parts, microcrystalline wax (paraffin brand No. 64#) 3.5 parts, chemical antiozonant (antioxidant 4020) 1.5 parts, composite internal anti-emetic cream (Struktol A60) 4 parts.
[0095] Example 4
[0096] 100 parts of butadiene rubber (Nd-BR, BR9000), 6.3 parts of naphthenic oil (KN4006), 38 parts of white carbon black (UltrasilVN3), 5.5 parts of silane coupling agent (Si-69), 3.3 parts of polyethylene glycol (PEG-4000), 6.6 parts of active zinc oxide ("Lianbo" brand), 0.63 parts of stearic acid (1801 type), 2.5 parts of sulfur masterbatch (Rhenogran S-80), 1.88 parts of accelerator CBS, 0.63 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 1.63 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 0 parts, microcrystalline wax (paraffin brand No. 64#) 3 parts, chemical antiozonant (antioxidant 4020) 1.5 parts, composite internal anti-emetic cream (Struktol A60) 3.1 parts.
[0097] Comparative Example 1
[0098] 30 parts of cis-butadiene rubber (Nd-BR, BR9000), 70 parts of styrene-butadiene rubber (SBR 1502), 10 parts of aromatic oil (DAE), 40 parts of conventional white carbon black (Zeosil 175C), 2 parts of silane coupling agent (Si-69), 5 parts of active zinc oxide ("Lianbo" brand), 2 parts of stearic acid (1801 type), 2 parts of sulfur powder, 1.5 parts of accelerator CBS, 0.3 parts of accelerator DPG, 2 parts of microcrystalline wax (paraffin wax grade 64#), 1 part of chemical antiozonant (antioxidant 4020).
[0099] Comparative Example 2
[0100] 100 parts of butadiene rubber (Nd-BR, BR9000), 6.3 parts of naphthenic oil (KN4006), 38 parts of white carbon black (UltrasilVN3), 0 parts of silane coupling agent (Si-69), 3.3 parts of polyethylene glycol (PEG-4000), 6.6 parts of active zinc oxide ("Lianbo" brand), 0.63 parts of stearic acid (1801 type), 2.5 parts of sulfur masterbatch (Rhenogran S-80), 1.88 parts of accelerator CBS, 0.63 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 1.63 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 4 parts, microcrystalline wax (paraffin brand No. 64#) 3 parts, chemical antiozonant (antioxidant 4020) 1.5 parts, composite internal anti-emetic cream (Struktol A60) 3.1 parts.
[0101] Comparative Example 3
[0102] 100 parts of butadiene rubber (Nd-BR, BR9000), 6.3 parts of naphthenic oil (KN4006), 38 parts of white carbon black (UltrasilVN3), 5.5 parts of silane coupling agent (Si-69), 0 parts of polyethylene glycol (PEG-4000), 6.6 parts of active zinc oxide ("Lianbo" brand), 0.63 parts of stearic acid (1801 type), 2.5 parts of sulfur masterbatch (Rhenogran S-80), 1.88 parts of accelerator CBS, 0.63 parts of accelerator TMTD masterbatch (Rhenogran TMTD-80), 1.63 parts of accelerator TBBS masterbatch (Rhenogran TBBS-80), hydrogenated petroleum resin (Escorez 5300) 4 parts, microcrystalline wax (paraffin brand No. 64#) 3 parts, chemical antiozonant (antioxidant 4020) 1.5 parts, composite internal anti-emetic cream (Struktol A60) 3.1 parts.
[0103] 4. Performance Testing Methods
[0104] The vulcanized rubber samples prepared in the above examples and comparative examples were subjected to performance tests according to the following test standards:
[0105] Hardness (Shore A): Tested in accordance with GB / T 531.1-2008.
[0106] Tensile strength and elongation at break: tested in accordance with GB / T 528-2009, with a tensile rate of 500 mm / min.
[0107] Right-angle tear strength: tested according to GB / T 529-2008 Method A.
[0108] DIN wear volume: Tested in accordance with GB / T 9867-2008 (load 10N, wear travel 40m).
[0109] Low temperature brittleness temperature: tested according to GB / T 15256-2014 method B.
[0110] -40°C Hardness Change: After placing the specimen in a low-temperature oven at -40°C ± 1°C for 2 hours, immediately measure its Shore A hardness and compare it to the hardness at room temperature (23°C ± 2°C). Calculate the change rate. Change rate = [(low-temperature hardness - room-temperature hardness) / room-temperature hardness] × 100%.
[0111] -70℃ hardness change rate: After the sample is placed in a low-temperature box at -70℃±2℃ for 2 hours, its Shore A hardness is quickly tested and compared with the hardness at room temperature (23±2℃), and the change rate is calculated.
[0112] Wet dynamic anti-slip coefficient: The test is conducted on a standard tile test surface (with water) in accordance with GB / T 3903.6-2017, and the dynamic friction coefficient of the forefoot and heel is recorded.
[0113] Ozone Aging Resistance: Tested according to GB / T 7762-2014, Method A (20% static tensile strength), at an ozone concentration of 50±5 pphm, a temperature of 40±2°C, and a test duration of 72 hours. Observe for cracks. Crack grade is assessed according to GB / T 7762-2014 (Grade 0: No cracks, Grade 1: Visible minor cracks, and so on).
[0114] Blooming observation: Place the vulcanized rubber sample at room temperature of 23±2℃ and relative humidity of 50±5% for 7 days, and then visually observe whether there is precipitation of compounding agent on the surface.
[0115] 5. Test Results and Analysis
[0116] Table 1: Performance test results of examples and comparative examples
[0117]
[0118] Result analysis:
[0119] Comparison of Examples 1-4 with Comparative Example 1:
[0120] Examples 1-4 all adopt the specific formulation system described in the present invention, including high cis-butadiene rubber, naphthenic oil, highly dispersed silica, sulfur-containing silane coupling agent, polyethylene glycol of specific molecular weight, and optimized vulcanization system and auxiliary additives.
[0121] As can be seen from the data in Table 1, compared with Comparative Example 1, which uses a conventional SBR / BR combination, aromatic oil, conventional white carbon black, a low amount of silane coupling agent, no PEG, and a conventional vulcanization system, Examples 1-4 show significant advantages in all performance aspects. In terms of low-temperature performance, the low-temperature brittle temperatures of Examples 1-4 are all much lower than those of Comparative Example 1 (for example, Example 1 is -75°C, while Comparative Example 1 is -45°C), indicating that the rubber of the present invention has superior low-temperature toughness. The hardness change rate at -40°C and -70°C is also significantly lower than that of Comparative Example 1 (for example, the hardness change rate of Example 1 at -70°C is +13.5%, while that of Comparative Example 1 is +32.5%), indicating that the rubber of the present invention can still maintain good flexibility at extreme low temperatures and is not easy to harden. In terms of anti-slip performance, the wet dynamic anti-slip coefficients of Examples 1-4 are all significantly higher than those of Comparative Example 1 (for example, Example 1 is 0.36 / 0.35, while that of Comparative Example 1 is 0.27 / 0.26), indicating that the rubber of the present invention has superior wet anti-slip ability. In terms of physical and mechanical properties, Examples 1-4 all outperformed Comparative Example 1 in terms of tensile strength, elongation at break, right-angle tear strength, and abrasion resistance (lower DIN abrasion volume). This is due to the synergistic effect of highly dispersed silica, silane coupling agent, and polyethylene glycol, which form a strong filler-rubber interface and an optimized reinforcement network. In terms of aging resistance and appearance, Examples 1-4 exhibited excellent ozone aging resistance (grade 0, no cracking) and showed no blooming, while Comparative Example 1 exhibited cracking and slight blooming.
[0122] Comparison between Example 1 and Comparative Example 2 (Effect of Silane Coupling Agent):
[0123] Comparative Example 2 is based on the formula of Example 1, but without the silane coupling agent Si-69. The test results show that the absence of the silane coupling agent leads to a sharp decrease in tensile strength, right-angle tear strength and abrasion resistance (DIN abrasion volume increases significantly to 150 mm). 3 This fully demonstrates the key role of silane coupling agents in forming an effective chemical bridge between silica and rubber, strengthening the interfacial bond, and thus achieving efficient reinforcement. Although the low-temperature performance and anti-slip coefficient are relatively less affected, the deterioration of mechanical properties will seriously affect the durability of the product.
[0124] Comparison of Example 1 and Comparative Example 3 (Effect of Polyethylene Glycol PEG-4000):
[0125] Comparative Example 3, based on the formulation of Example 1, removed PEG-4000. The results showed that while the absence of PEG-4000 still improved various properties compared to Comparative Example 1, its physical and mechanical properties (such as tensile strength, tear strength, and abrasion resistance) declined to a certain extent compared to Example 1, and the rate of change in hardness at low temperatures increased slightly. This suggests that PEG-4000 has a positive effect on improving the dispersion of silica in rubber, promoting the reaction between the silane coupling agent and silica, and thus further optimizing the reinforcement effect.
[0126] Internal comparison of Examples 1-4:
[0127] Example 1 represents a preferred intermediate formulation of the present invention. Example 2 uses lower amounts of each main component. Although the performance is slightly lower than that of Example 1, it is still better than the comparative example in all aspects. Example 3 uses higher amounts of each main component and exhibits more excellent comprehensive performance, especially in terms of mechanical properties and low-temperature performance. Compared with Example 1, Example 4 does not add hydrogenated petroleum resin, and its physical and mechanical properties are slightly reduced, indicating that hydrogenated petroleum resin has a certain auxiliary contribution to hardness and reinforcement. These examples together verify the effectiveness of the component range defined by the present invention.
[0128] In summary, the present invention successfully prepares a cold-resistant and anti-slip rubber with excellent low-temperature performance, outstanding anti-slip performance, good physical and mechanical properties and durability through the optimized combination of specific components, especially the synergistic effect of high-cis-butadiene rubber, naphthenic oil, highly dispersed silica, sulfur-containing silane coupling agent and specific molecular weight polyethylene glycol, and in combination with an optimized vulcanization system and functional additives.
[0129] The above description and embodiments are intended to explain the scope of protection of the present invention, but do not constitute a limitation thereto. Modifications, equivalent substitutions, or other improvements to the embodiments of the present invention or portions thereof that can be obtained by a person of ordinary skill in the art through logical analysis, reasoning, or limited experimentation based on the teachings of the present invention or the above embodiments, combined with common knowledge, ordinary technical knowledge in the field, and / or prior art, should all be included within the scope of protection of the present invention.
Claims
1. A cold-resistant anti-slip rubber, characterized in that it comprises the following components: 80-110 parts by weight of diene rubber; 5-8 parts by weight of naphthenic oil; 35-45 parts by weight of carbon black; 5-6 parts by weight of silane coupling agent; 3-4 parts by weight of polyethylene glycol with a molecular weight range of 3500-4400; and a vulcanization system.
2. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The vulcanization system comprises: An active agent comprising 6-7 parts by weight of active zinc oxide and 0.5-1 parts by weight of stearic acid; a vulcanizing agent, which is 2-3 parts by weight of sulfur masterbatch pre-dispersed with an inert carrier; and The composite accelerator comprises 1.5-2.0 parts by weight of N-cyclohexyl-2-benzothiazole sulfenamide, 0.5-1.0 parts by weight of tetramethylthiuram disulfide pre-dispersed with an inert carrier, and 1.5-2.0 parts by weight of N-tert-butyl-2-benzothiazole sulfenamide pre-dispersed with an inert carrier.
3. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The diene rubber is butadiene rubber, and the cis-1,4 structure content thereof is greater than or equal to 96%.
4. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The silane coupling agent is a sulfur-containing silane coupling agent.
5. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The invention also comprises 3-5 parts by weight of hydrogenated petroleum resin, wherein the softening point of the hydrogenated petroleum resin is 100±5°C.
6. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The invention also includes 4-5 parts by weight of an anti-cracking agent, which is a compound of microcrystalline wax and a chemical antiozonant.
7. The cold-resistant anti-slip rubber according to claim 1, characterized in that: The invention also comprises 3-4 parts by weight of a composite internal anti-emetic cream, which is composed of high molecular weight fatty acid ester and polyol ester.
8. A method for preparing cold-resistant anti-slip rubber, characterized in that: The following steps are involved: High-temperature one-stage mixing: mixing the diene rubber, the naphthenic oil, the white carbon black, the silane coupling agent, the polyethylene glycol, and other additives except the vulcanization system in an internal mixer, with the discharge temperature controlled in the range of 100-130° C., to obtain a masterbatch; Low-temperature second-stage mixing: After the masterbatch obtained in the previous step is cooled to a rubber temperature below 60°C, the vulcanization system is added and mixed at a mixing temperature of 50-65°C, and the rubber temperature is ensured not to exceed 90°C to obtain a final rubber mix; Sheeting and storage: The final rubber mix obtained in the previous step is rolled out into sheets and stored in an environment with controlled room temperature and relative humidity for 12-24 hours; as well as Vulcanization molding: Place the rubber material after the previous step into the mold and perform vulcanization molding at a temperature of 150-170°C and a pressure of 8-15MPa.
9. The method for preparing a cold-resistant anti-slip rubber according to claim 8, characterized in that: The debinding temperature in the high-temperature first-stage mixing is controlled at 115±5°C.
10. The method for preparing cold-resistant anti-slip rubber according to claim 8, characterized in that: The vulcanization molding adopts a segmented vulcanization process, including: performing a first stage vulcanization for 180-220 seconds at a temperature of 160° C. and a pressure of 12 MPa, and then continuing a second stage vulcanization for 450-510 seconds without changing the temperature and pressure.